2011
DOI: 10.1371/journal.pone.0027173
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Metagenomic-Guided Whole-Community Proteomics of Complex Microbial Environments

Abstract: Accurate protein identification in large-scale proteomics experiments relies upon a detailed, accurate protein catalogue, which is derived from predictions of open reading frames based on genome sequence data. Integration of mass spectrometry-based proteomics data with computational proteome predictions from environmental metagenomic sequences has been challenging because of the variable overlap between proteomic datasets and corresponding short-read nucleotide sequence data. In this study, we have benchmarked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 39 publications
0
72
0
Order By: Relevance
“…The 2D-DIGE strategy further solved the specific question of detecting differences between groups, a problem that faces even greater challenges in label-free shotgun metaproteomics. [26][27][28][29][30][31] A set of proteins from members of the Bacteroidetes phylum, largely Bacteroides species, were over-represented in CD microbiota. By contrast, under-represented proteins were mostly from Clostridiales (Firmicutes phylum), and more rarely from Prevotella and undefined Bacteroidales members.…”
Section: Discussionmentioning
confidence: 99%
“…The 2D-DIGE strategy further solved the specific question of detecting differences between groups, a problem that faces even greater challenges in label-free shotgun metaproteomics. [26][27][28][29][30][31] A set of proteins from members of the Bacteroidetes phylum, largely Bacteroides species, were over-represented in CD microbiota. By contrast, under-represented proteins were mostly from Clostridiales (Firmicutes phylum), and more rarely from Prevotella and undefined Bacteroidales members.…”
Section: Discussionmentioning
confidence: 99%
“…Protein profiles will be measured by two-dimensional nano liquid chromatography (2D-LC) and tandem mass spectrometry (MS/MS) (Cantarel et al, 2011; Presley et al, 2012), with proteins identified by searching custom databases consisting of the human genome, matched metagenomes from the same samples, and a defined set of reference genomes, including many that are in the HMP reference genome database. Based on preliminary results, it is anticipated that > 3,000 proteins will be identified per sample and that approximately half of the proteins will be human proteins based on a pretested method for preparation of the protein extracts.…”
Section: Ihmp Study: Characterizing the Gut Microbial Ecosystem For Dmentioning
confidence: 99%
“…At first, Verberkmoes et al (2009b) published an analysis employing relative protein abundances (normalized spectral) for a comparison of two fecal samples and two distinct sequence databases. Cantarel et al (2011) used the same samples to test several computational strategies to improve protein identification. A new iterative workflow for protein identification leads to an increase of Clusters of Orthologous Groups (COG) categories (Rooijers et al, 2011).…”
Section: Label-free Approachesmentioning
confidence: 99%